Haematological response and growth performance of Nile tilapia (Oreochromis niloticus L.) fed diets containing folic acid - Barros, Margarida Maria [UNESP]; Tavares Ranzani-Paiva, Maria Jose; Pezzato, Luiz Edivaldo [UNESP]; Falcon, Dario Rocha; Guimaraes, Igo Gomes (Wiley-Blackwell Publishing, Inc, 2009)
Haematological response and growth performance over 150 days, and resistance to a low-temperature stress of Nile tilapia fed diets with increasing folic acid (FA) levels were evaluated. The experiment was conducted in a completely randomized design with eight FA levels (0.0, 0.5, 1.0, 2.0, 3.0, 4.0, 5.0 and 6.0 mg kg(-1) feed) supplemented in purified diets (32.0% CP and 13 398 kj DE kg(-1)). One hundred and ninety-two fingerlings were randomly assigned to 32 net cages distributed in eight 1000 L aquaria with a physical and biological filter and a temperature control system (26.0 +/- 1.0 degrees C). For cold-induced stress, fish were transferred to 24 30 L-aquaria with individual biofilters and aeration. The water temperature was gradually reduced until it reached 13 degrees C. Haematological parameters evaluated before and after cold stress were total erythrocytes and leucocytes count, differential leucocyte, haemoglobin, haematocrit, total plasmatic protein and haematometric indices. Growth performance parameters were mean weight gain, feed conversion ratio and survival. Dietary FA supplementation did not influence erythropoiesis under normal temperature conditions; cold stress impaired erythropoiesis, causing hypochromic microcytic anaemia and leucopoiesis, and also neutrophilia. Growth performance is influenced by folate and supplementation between 0.5 and 1.0 mg FA kg(-1) diet, which makes up for nutritional demands, guaranteeing production and health under appropriate temperature conditions.
Keywords: folic acid; Nile tilapia; haematology; growth